Effect of Service Quality, Received Value, and Company Image on Customer Satisfaction Savings in PT. Bank Aceh Center Banda Aceh - Jamil, Muhammad; Jamali (Indonesian Journal Economic Review (IJER), 2021)
The research was conducted to investigate the effect of service quality, perceived value, and the corporate image on consumer satisfaction in Bank Aceh. The sample used in this research was 177 people total customer savings of the population saving customers that saving in Bank Aceh. Primary data were collected by distributing the sheets of questions (questionnaire) conducted by the convenience sampling method. This research used multiple linear regression. Hypothesis testing was done by using a statistical test that is partially (t-test) and simultaneously (F test) with a significance level (a) of 5%. The results showed that the independent variables consisting of the variable service quality, perceived value, and the corporate image affects customer satisfaction savings on PT Bank Aceh either partially (t-test) or simultaneously (F test). Variable service quality was the most influential variable on customer satisfaction at PT Bank Aceh.